Specific Features of Using Abbreviation in English Military Discourse - Avyasova Irina (Zien Journals, 2022)
The article introduces of the work is due to the fact that the socio-stylistic characteristics of a vast layer of abbreviated vocabulary, including aviation military vocabulary, is one of the most important and little-studied issues of interaction between society and language, and the study of abbreviated word formation in the military sphere is part of the general problem of secondary nomination and vocabulary expansion of the language. Vocabulary is the language system that reacts most quickly and adequately with its new formations to changes taking place in society. This is especially true in the military area. The purpose of the study in the article is to identify similarities and differences in the structure and semantics of military abbreviations in modern English. The features of abbreviation in the English military aviation discourse are highlighted.
Keywords: abbreviation; military; aviation; discourse